CD26/dipeptidylpeptidase IV—chemokine interactions: double‐edged regulation of inflammation and tumor biology. Issue 6 (7th January 2016) - Mortier, Anneleen; Gouwy, Mieke; Van Damme, Jo; Proost, Paul; Struyf, Sofie
Abstract : Review of how chemokine processing by CD26/DPP IV regulates leukocyte trafficking. Abstract : Post‐translational modification of chemokines is an essential regulatory mechanism to enhance or dampen the inflammatory response. CD26/dipeptidylpeptidase IV, ubiquitously expressed in tissues and blood, removes NH2 ‐terminal dipeptides from proteins with a penultimate Pro or Ala. A large number of human chemokines, including CXCL2, CXCL6, CXCL9, CXCL10, CXCL11, CXCL12, CCL3L1, CCL4, CCL5, CCL11, CCL14, and CCL22, are cleaved by CD26; however, the efficiency is clearly influenced by the amino acids surrounding the cleavage site and although not yet proven, potentially affected by the chemokine concentration and interactions with third molecules. NH2 ‐terminal cleavage of chemokines by CD26 has prominent effects on their receptor binding, signaling, and hence, in vitro and in vivo biologic activities. However, rather than having a similar result, the outcome of NH2 ‐terminal truncation is highly diverse. Either no difference in activity or drastic alterations in receptor recognition/specificity and hence, chemotactic activity are observed. Analogously, chemokine‐dependent inhibition of HIV infection is enhanced (for CCL3L1 and CCL5) or decreased (for CXCL12) by CD26 cleavage. The occurrence of CD26‐processed chemokine isoforms in plasma underscores the importance of the in vitro‐observed CD26 cleavages. Through modulation of chemokine activity, CD26 regulates leukocyte/tumor cell migration and progenitor cell release from the bone marrow, as shown by use of mice treated with CD26 inhibitors or CD26 knockout mice. As chemokine processing by CD26 has a significant impact on physiologic and pathologic processes, application of CD26 inhibitors to affect chemokine function is currently explored, e.g., as add‐on therapy in viral infection and cancer.